Aplikasi Microsoft Excel pada Musik Dodekafon Matriks - Immanuel Katharo Pasaribu; Dimas Phetorant (Journal of Music Science, Technology, and Industry, 2021)
Purpose: This paper discusses the Microsof Excel application on matrix dodeka music. Dodekafon can not be separated from Schoenberg. Dodekafon has its own rules. Music that is less popular with ordinary people. Research methods: This research method uses a qualitative approach, in the form of literature study and analyze. The use of matrices in mathematical calculations is applied in one application, with formulas in the exel application. Results and discussion: This formula produces a matrix table, which functions to analyze and create dodekafon music. Implication: This research aims to show how technology provides new colors and ways in the process of creating musical compositions.